Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 9 - 9.2 - Two-Variable Linear Systems - 9.2 Exercises - Page 646: 19



Work Step by Step

Multiplying equation 2 by -3, and equation 1 by 2, we get: $6x+4y=20$ and $-6x-15y=-9$ Adding both equations, we get $-11y=11$ and thus $y=-1$ (Elimination) Substituting the value of y in equation 1: $6x-4=20$ This becomes $6x=20+4=24$ and $x=4$ Thus, we get $(4,-1)$ as a solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.